Evaluation of breast amorphous calcifications by a computer-aided detection system in full-field digital mammography - Scaranelo, A M (The British Institute of Radiology., 2012)
OBJECTIVES: The purpose of this study was to evaluate the performance of a direct computer-aided detection (d-CAD) system integrated with full-field digital mammography (FFDM) in assessment of amorphous calcifications. METHODS: From 1438 consecutive stereotactic-guided biopsies, FFDM images with amorphous calcifications were selected for retrospective evaluation by d-CAD in 122 females (mean age, 56 years; range, 35–84 years). The sensitivity, specificity, accuracy and false-positive rate of the d-CAD system were calculated in the total group of 124 lesions and in the subgroups based on breast density, mammographic lesion distribution and extension. Logistic regression analysis was used to stratify the risk of malignancy by patient risk factors and age. RESULTS: The d-CAD marked all (36/36) breast cancers, 85% (11/13) of the high-risk lesions and 80% (60/75) of benign amorphous calcifications (p<0.01) correctly. The sensitivity, specificity and diagnostic accuracy for the combined malignant and “high-risk” lesions was 96, 80 and 86%, respectively. The likelihood of malignancy was 29%. There was no significant difference between the marking of fatty or dense breasts (p>0.05); however, d-CAD marks showed differences for small (<7 mm) lesions (p=0.02) and clustered calcifications (p=0.03). The false-positive rate of d-CAD was 1.76 marks per full examination. CONCLUSION: The d-CAD system correctly marked all biopsy-proven breast cancers and a large number of biopsy-proven high-risk lesions that presented as amorphous calcifications. Given our 29% likelihood of malignancy, imaging-guided biopsy appears to be a reasonable recommendation in cases of amorphous calcifications marked by d-CAD.